A case of nocardia keratitis treated successfully with topical amikacin - Bajracharya, L; Gurung, R (Nepalese Journal of Ophthalmology, 2012)
Background: Keratitis caused by the nocardia species is rare in clinical practice and can cause confusion during treatment because it often mimics fungal keratitis. Case: This is a case of nocardia keratitis occurring in a forty-year-old lady without any predisposing factors. It was initially treated as fungal keratitis, then as herpes simplex viral keratitis, but once the organism was known, it was successfully treated with topical fortified amikacin 14 mg/ml (1.4 %). Conclusion: Delay in diagnosis can occur in nocardia keratitis due to its rarity in occurrence. It responds well if proper therapy is instituted on time. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5870 NEPJOPH 2012; 4(1): 170-173